Analisis Pengaruh Panas dan Beban terhadap Kerusakan Traveling Grate pada Boiler Di PLTU Tembilahan 2x7 MW - Sandi Saputra; Siswo Pranoto; Yopan Rahmad Aldori; Syurkarni Ali; Junaidi; Andri Herlambang; Muhammad Yusuf Rahmansyah Siahaan; Muhammad Idris (Universitas Medan Area, 2023)
Rack grate is a component composed of rack clip and rack bone arrangement that serves as a dropping cross-section media of coal and as a media of coal burned in the boiler.Â As part of the main component, the rack grate can be regarded as one of the components that ensure the success of combustion in the boiler. Failure to this component will certainly interfere with the implementation of boiler operations. In addition to require the boiler to be shut down while repaired, in addition to requiring the boiler to be extinguished during repairs, the inoperability of the boiler makes the steam production process at the PLTU impossible and ultimately the electricity generation process cannot be carried out as usual. Damage to the rack grate component has a type of plastic deformation with variable loads and fluctuating heat, which means that the thermal stress in the system has reached the yield stress point. To find out the root cause of this component damage quickly and accurately, an analysis of the results of the implementation of engineering software in this case Ansys Workbench, and a comparison of actual operating data, and data design is the best choice. Lastly, by evaluating the optimum values of temperature, equivalent stress and strain, total deformation, input process parameters value can be controlled to the desired values, resulting in less stress concentration occurs, so that the damage to the workpiece can be reduced or even eliminated.